Joseph Conrad and H. G. Wells - Dryden, L. author. aut Link
X, 216 p.
Keywords: This book traces the literary friendship between Joseph Conrad and H. G. Wells from their early correspondence through to the differences that caused their estrangement, including their respective responses to the First World War. It thus gives an overview of the literary scene in the late Victorian and early Edwardian period.